Disordered eating behaviours and autistic traits—Are there any associations in nonclinical populations? A systematic review. (30th July 2018) - Christensen, Stephanie Stensbjerg; Bentz, Mette; Clemmensen, Lars; Strandberg‐Larsen, Katrine; Olsen, Else Marie
Abstract: Objective: The objective of this study is to critically review existing literature concerning the possible association between autistic‐like behaviours and problematic eating behaviours in nonclinical populations. Method: We performed a systematic literature search in three large databases. Studies were included if they assessed any association between a broad range of autistic‐like behaviours and problematic eating behaviours in nonclinical samples. Results: Sixteen eligible studies were found covering 3, 595 participants in total, including five studies on children/adolescents ( n  = 685). All studies were cross‐sectional, and thus, only concurrent associations could be evaluated. Several autistic‐like behaviours were found to be associated with problematic eating behaviours, with the overall "autism spectrum quotient, " deficiencies in set‐shifting, and theory of mind showing the strongest associations. Conclusions: The existing literature indicates concurrent associations between specific autistic‐like behaviours and problematic eating behaviours in nonclinical samples across ages. Large prospective longitudinal studies are needed for insight into the temporal order of these associations.